Hungarian Monitoring, 27 May 1988 . [Magyar rádiófigyelő], 1988. május 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Missile agreement vote in Senate - NATO meeting in Brussels - Searching for a way out of Polish economic crisis - German-German relations Domestic Affairs: - Alois Mock's schedule in Hungary - Protest against Gabčíkovo-Nagymaros dam - FRG to cancel compulsory visas between the two Germanies - 3rd edition of 'The History of Transylvania' Economy: - Fall in number of employees in agriculture Külpolitika - Rakétaszerződés szavazás a Szenátusban - Brüsszeli NATO értekezlet - Kiútkeresés a lengyel gazdasági válságból - Német-német kapcsolatok Belpolitika - Alois Mock magyarországi programja - Tiltakozás a Bős-Nagymarosi Vízlépcső ellen - Az NSZK megszüntetné a két ország közötti vízumkényszert - Erdély története 3. kiadás Gazdaság: - Csökken a foglalkoztatottak száma a mezőgazdaságban